Investigation on the mechanical and microstructure properties of masonry cement-red mud-carbide slag-based paste - Xiaoqian Cen; Yaqing Zhang; Hongen Zhang (Case Studies in Construction Materials)
The high alkalinity and complex phase composition of red mud pose significant challenges for its direct utilization. The construction industry is widely regarded as the most viable option for large-scale consumption of red mud to mitigate its continuous accumulation globally. Activation treatment is a crucial prerequisite for preparing cementitious materials from red mud, but traditional methods either require high-temperature calcination of red mud or the use of substantial amounts of strong alkaline substances as alkaline activators, thereby increasing costs and hindering the large-scale application of red mud. This paper presents an alternative method where 4 % carbide slag is used as an activator to prepare cement-red mud-carbide slag-based composite pastes, substituting 10 %-90 % of masonry cement with red mud. As the red mud content increases, the compressive and flexural strengths of the hydrated pastes significantly decrease; the compressive strength of the material with 10 % red mud is 13.4 times that of the material with 90 % red mud. The addition of 4 % carbide slag enhances the compressive and flexural strengths of the red mud-based cementitious material, with increases of 1.67 %, 17.9 %, and 34.6 % in compressive strength at 3d, 7d, and 28d, respectively, and increases of 2.38 %, 6.67 %, and 7.36 % in flexural strength. This indicates that carbide slag is beneficial for activating the reactivity of red mud. There is an incremental correlation between the flexural and compressive strength of the cementitious material, and a fitting formula can be employed to quantify the relationship between red mud content and these strengths. Microstructural analysis confirms that the addition of carbide slag significantly optimizes the pore structure, promoting the formation of Ca(OH)2 and C-S-H gel, which leads to improved mechanical properties of the red mud-containing composites. This study provides a feasible solution for the extensive application of red mud within the cement industry.